2, 2‐Bis(5‐tetrazolyl)propane as Ligand in Energetic 3d Transition Metal Complexes. Issue 3 (11th September 2018) - Szimhardt, Norbert; Gruhne, Michael S.; Lommel, Marcus; Hess, Andreas; Wurzenberger, Maximilian H. H.; Klapötke, Thomas M.; Stierstorfer, Jörg
Abstract : This contribution covers the preparation and characterization of 2, 2‐bis(5‐tetrazolyl)propane (5‐DTP) (1 ). The bridged bitetrazole is used as a neutral nitrogen‐rich ligand in 3d transition metal(II) based complexes for the first time and can be synthesized via [2+3] cycloaddition from sodium azide and dimethylmalononitrile. The combination with different anions (e.g., perchlorate, nitrate, sulfate, and chloride) yields materials with widely varying physicochemical properties. The obtained coordination compounds were characterized using low‐temperature single‐crystal X‐ray diffraction (except14 ), IR spectroscopy, elemental analysis, and DTA (except16 ). The sensitivities toward external stimuli (impact and friction) were determined according to the Bundesamt für Materialforschung und ‐prüfung (BAM) standard methods together with its sensitivities against electrostatic discharge (except16 ). Complexes10 and14 were characterized in laser ignition experiments. For determination of the compounds' deflagration to detonation transition (DDT) capability, hot plate and hot needle tests were performed for the zinc(II) and copper(II) perchlorate complexes. Abstract :